2015
DOI: 10.1016/j.resuscitation.2014.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function and health-related quality of life four years after cardiac arrest

Abstract: Cognitive impairment four years after cardiac arrest affected more than one quarter of the patients. Short-term memory was predominantly affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 29 publications
3
58
0
5
Order By: Relevance
“…Neurocognitive testing was completed with the Cambridge Neuropsychological Test Automated Battery (CANTAB) at a median of 3.6 years after CA. The pattern of predominant spatial memory impairment seen in these patients was suggestive of early AD-type temporal lobe dysfunction [14].…”
Section: The Range Of Cognitive Impairment and Dysfunction After Cardmentioning
confidence: 84%
See 3 more Smart Citations
“…Neurocognitive testing was completed with the Cambridge Neuropsychological Test Automated Battery (CANTAB) at a median of 3.6 years after CA. The pattern of predominant spatial memory impairment seen in these patients was suggestive of early AD-type temporal lobe dysfunction [14].…”
Section: The Range Of Cognitive Impairment and Dysfunction After Cardmentioning
confidence: 84%
“…There was no statistically significant difference seen in cognitive function between the 33°and 36°group, which called into question the neuroprotective effect of therapeutic hypothermia (TH). Other studies have shown that treatment with TH did not predict long-term cognitive function in a cohort of patients tested 4 years after cardiac arrest [14]. When compared to cardiac arrest survivors, the control group (STEMI survivors) showed a similar level of cognitive dysfunction in memory and executive dysfunction, with better performance only in attention and processing speed by the Symbol Digital Modalities Test (SDMT) [55].…”
Section: The Effect Of Targeted Temperature Management On Cognitive Amentioning
confidence: 95%
See 2 more Smart Citations
“…HRQoL has, however, been studied extensively in cardiac arrest survivors and ICD patients in general. Although results in cardiac arrest survivors are heterogeneous, a recent meta‐analysis showed that the majority of cardiac arrest survivors report a good HRQoL . In addition, ICD patients in general, with both a primary and secondary prevention indication, report a normal HRQoL .…”
Section: Discussionmentioning
confidence: 99%